Endogenous retroviral gene elements (syncytin-Rum1 and BERV-K1), interferon-τ, and pregnancy associated glycoprotein-1 are differentially expressed in maternal and fetal tissues during the first 50 days of gestation in beef heifers. Issue 3 (1st September 2017) - McLean, K. J.; Crouse, M. S.; Crosswhite, M. R.; Black, D. N.; Dahlen, C. R.; Borowicz, P. P.; Reynolds, L. P.; Ward, A. K.; Neville, B. W.; Caton, J. S.
Abstract: We hypothesized that the endogenous retroviruses [ERV: syncytin-Rum1 and ( BERV-K1 )], and pregnancy hormones [ interferon -τ ( IFN -τ), and pregnancy associated glycoprotein-1 ( PAG-1 )] would be differentially expressed whereas progesterone and insulin concentrations in maternal blood would remain steady during early gestation. To test this hypothesis Angus crossbred heifers ( n = 46; ∼15 mo of age; BW = 363 ± 35 kg) were fed native grass hay, supplemented with cracked corn to gain 0.3 kg/d, and given ad libitum access to water. All heifers were subjected to a 5-d CO-Synch + CIDR estrous synchronization protocol and AI (breeding = d 0). Ovariohysterectomies were performed on d 16, 22, 28, 34, 40, and 50 of gestation and at d 16 of the estrous cycle for non-pregnant (NP) controls. Utero-placental tissues [maternal caruncle (CAR); maternal intercaruncular endometrium (ICAR); and fetal membranes, (FM, chorion on d 16, chorioallantois on d 22 to 50)] were collected from the uterine horn ipsilateral to the corpus luteum (CL). Tissues were flash frozen and stored at –80°C. Expression of mRNA was evaluated using qPCR. In CAR, syncytin-Rum1 expression was greater ( P < 0.01) on d 50 (81.5-fold) compared with NP controls or any other day of early pregnancy. In contrast, syncytin-Rum1 expression in I-CAR only tended ( P = 0.09) to change across days of early pregnancy and did not differ ( P = 0.27) in FM tissues. In CAR, the expression of BERV-K1 was not different ( P > 0.79) at d 16 and 22, was intermediate at d 28, 34, and 40, and was greatest on d 50 (108-fold increase compared with NP). Expression of BERV-K1 in FM was increased ( P < 0.01) on d 28, 34, and 50 compared with NP controls, but at d 40 did not differ from NP controls. The mRNA expression of IFN -τ in FM at d 22 was greater ( P < 0.01) than all other days of gestation. In CAR, expression of PAG-1 increased ( P < 0.001) dramatically on d 40 (20, 000-fold) and d 50 (86, 000-fold) compared with NP heifers ( P < 0.01). In ICAR, expression of PAG-1 was greater ( P < 0.05) on d 28 and 40 (fold increases of 113 and 102, respectively, compared with NP). Insulin concentrations were not different ( P = 0.53) but progesterone was greater ( P < 0.01) on d 16, 22, 28, 34, and 40 compared with d 50 of gestation. These data confirm differential ERV, IFN -τ, and PAG-1 gene expression during critical time points of early gestation in utero-placental tissues.